2018
DOI: 10.11645/12.1.2349
|View full text |Cite
|
Sign up to set email alerts
|

Using a flipped classroom to embed information literacy skills training into academic studies

Abstract: Dommett, E. 2018. Using a flipped classroom to embed information literacy skills training into academic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Journal Country h-Index [43] Communications in Information Literacy United States 14 [44] Journal of the Medical Library Association United States 57 [45] Pixel-Bit. Revista de Medios y Educación Spain 2 [46] Journal of Information Literacy United Kingdom 9 [47] Journal of Information Literacy United Kingdom 9 [48] Journal of Information Literacy United Kingdom 9 [49] Journal of the Medical Library Association United States 57 [50] Journal of Information Literacy United Kingdom 9 [51] Australian Academic & Research Libraries Australia 25 [52] The Journal of Academic Librarianship United Kingdom 55 [53] Communications in Informational Literacy United States 14 In terms of the discipline of knowledge to which the analyzed studies belonged (Table 3), they mainly belonged to the branch of knowledge "Information Science and Library Science" followed by "Computer Sciences" with "Medical Informatics" and "Educational Research". As for the institutions from which the authors come, they are varied, a large part of them coming from the United States.…”
Section: Referencesmentioning
confidence: 99%
“…Journal Country h-Index [43] Communications in Information Literacy United States 14 [44] Journal of the Medical Library Association United States 57 [45] Pixel-Bit. Revista de Medios y Educación Spain 2 [46] Journal of Information Literacy United Kingdom 9 [47] Journal of Information Literacy United Kingdom 9 [48] Journal of Information Literacy United Kingdom 9 [49] Journal of the Medical Library Association United States 57 [50] Journal of Information Literacy United Kingdom 9 [51] Australian Academic & Research Libraries Australia 25 [52] The Journal of Academic Librarianship United Kingdom 55 [53] Communications in Informational Literacy United States 14 In terms of the discipline of knowledge to which the analyzed studies belonged (Table 3), they mainly belonged to the branch of knowledge "Information Science and Library Science" followed by "Computer Sciences" with "Medical Informatics" and "Educational Research". As for the institutions from which the authors come, they are varied, a large part of them coming from the United States.…”
Section: Referencesmentioning
confidence: 99%
“…The literature also showed that any negative impact of a change to flipped learning would be minimal. Studies have found that flipped IL instruction results in positive student feedback and either slightly improves academic outcomes or does not significantly impact on them (Arnold-Garza, 2014;Brooks, 2014;McCue, 2016;Dommett;2018;Poole, 2021). While the challenges of assessing the impact of IL instruction have rightly been noted (Markless & Streatfield, 2017), it is equally true that effective, well-studied historic tuition models would fall under a broad definition of flipped learning (Abeysekera & Dawson, 2016).…”
Section: Wider Environmentmentioning
confidence: 99%
“…Teachers can modify the teaching-learning conditions through the flipped classroom because this pedagogical model allows the creation of dynamic, creative and active activities (Cohen et al, 2016;Maciejewski, 2016). For example, students make presentations and discuss the topics of the courses in the classroom (Dommett, 2018). Several authors (e.g., Mason et al, 2013;Maciejewski, 2016;Salinas Martínez et al, 2015;Shen, 2018) have incorporated the flipped classroom in school activities and educational practices.…”
Section: Flipped Classroommentioning
confidence: 99%
“…In the same way, Cohen et al (2016) used the flipped classroom to facilitate the assimilation of knowledge about the use of digital resources. Even, Dommett (2018) incorporated digital readings and videos into school activities for developing students' skills.…”
Section: Flipped Classroommentioning
confidence: 99%